2016
DOI: 10.1002/ejoc.201501544
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Pd‐Catalyzed Cascade Reactions of Cyclic Diaryliodoniums and Alkynes – Access to Fluorenes with Conjugate Enynes/Dienes

Abstract: Unlike the widely studied linear diaryliodoniums as electrophilic arylating reagents, cyclic diaryliodoniums have the potential to initiate dual arylations with atom and step economy. In our current work, cascade reactions of cyclic diaryliodoniums and two equivalent alkynes have been successfully achieved under mild conditions, catalyzed by CuI/PdCl2(PPh3)2. The transformation could also be realized in a stepwise way with two different alkynes or with one alkyne and one alkene. The reaction enables a rapid ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
(10 reference statements)
0
11
2
Order By: Relevance
“…CDPIs can react with various nucleophiles including reactive carbon, nitrogen, and sulfur, leading to the formation of polycyclic frameworks (Scheme ). These obtained polycycles are often heavily hydrocarbon-oriented and lipophilic . In the drug discovery field, heterocyclic frameworks with a considerable number of heteroatoms are in demand to gain the druggability of pharmacologically active compounds .…”
mentioning
confidence: 99%
“…CDPIs can react with various nucleophiles including reactive carbon, nitrogen, and sulfur, leading to the formation of polycyclic frameworks (Scheme ). These obtained polycycles are often heavily hydrocarbon-oriented and lipophilic . In the drug discovery field, heterocyclic frameworks with a considerable number of heteroatoms are in demand to gain the druggability of pharmacologically active compounds .…”
mentioning
confidence: 99%
“…In their earlier study, Liu et al 56 found that cyclic diaryliodonium salt 4 and p -tolyl acetylene 9 could be used to produce 4-fold fluorenes 10 , which were previously developed accidentally. The authors attempted their previous investigation with the objective of finding an alternative to aliphatic diaryliodonium's inefficient mechanism and unwanted iodoarene side product.…”
Section: Applications Of Cyclic Diaryliodonium Saltsmentioning
confidence: 99%
“…This strategy has been then extended to the preparation of alkyne-substituted alkylidenefluorenes 53 by replacing the arylboronic acid with a second equivalent of the terminal alkyne and performing the reaction at 35 °C ( Scheme 18 ) [ 58 ].…”
Section: Reviewmentioning
confidence: 99%